Meaning-Making Through Creativity During COVID-19 - Kapoor, Hansika; Kaufman, James C. (Frontiers in Psychology, 2020)
The COVID-19 pandemic resulted in an abrupt change in routines and livelihoods all around the world. This public health crisis amplified a number of systemic inequalities that led to populations needing to grapple with universally difficult truths. Yet some individuals, firms, and countries displayed resilient and creative responses in coping with pressing demands on healthcare and basic sanity. Past work has suggested that engaging in creative acts can be an adaptive response to a changing environment. Therefore, the purpose of this paper is to describe how entities at the personal, community, and national levels cultivated and expressed creativity in an effort to make meaning during COVID-19. By overlaying the Four C model of creativity on such responses, we aim to (a) to connect mini, little, Pro, and Big creative behaviors with our attempts to make meaning of the ongoing COVID-19 pandemic, and (b) to suggest how engaging in creative expression can be used to guard against the adverse consequences of this outbreak. Acknowledging that this time has been and continues to be distressing and filled with uncertainty, we propose some ways of making sense of current events by applying original thinking across domains. Further, we propose how engaging in creativity can serve to buffer against the negative effects of living through the pandemic.